The Barbiana school. The fortunate school experience of a «superobedient rebel» priest in the emancipation of the last - Betti, Carmen (Historia y Memoria de la Educación, 2018)
The purpose of this analysis is to demonstrate the singularity of the school opened by don Milani in an isolated area of the Tuscan countryside, called Barbiana, between 1958 and 1967. This experience, considered a didactic and pedagogic laboratory of interest at a national and international level, still causes controversy to this day. The experiment benefittted from a precedent, namely, the popular education experiment carried out in San Donato in Calenzano, near Prato, between 1947 and 1954